2012
DOI: 10.1002/iroh.201111490
|View full text |Cite|
|
Sign up to set email alerts
|

Distribution and Local Species Diversity of Freshwater Ostracoda in Relation to Habitat in the Kahramanmaraş Province of Turkey

Abstract: To understand the relationship between local (alpha) diversity of ostracods and their distribution, 95 different locations were randomly sampled from southern Kahramanmaraş (Turkey) between 7 June and 31 July, 2010. Total of 46 ostracods were encountered from 68 sites. Four alpha diversity indices (Shannon‐Wiener, Menhinick, Brillouin, Margalef) individually quantified higher species diversity and evenness for three types of habitats (limnocrene springs, ponds, stream). Diversity partitioning analyses revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
11
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 28 publications
6
11
1
Order By: Relevance
“…As previously stated (e.g., KÜlkÖylÜoğlu et al 2012c, Yavuzatmaca et al 2017a, the high species diversity was reported in the mid-elevational interval in the present study (Table 2). Whereas the finding of high diversity at low (e.g., Pèrez et al 2015 and high (e.g., KÜlkÖylÜoğlu et al 2012aKÜlkÖylÜoğlu et al , 2016 elevational intervals are also available in the literature.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As previously stated (e.g., KÜlkÖylÜoğlu et al 2012c, Yavuzatmaca et al 2017a, the high species diversity was reported in the mid-elevational interval in the present study (Table 2). Whereas the finding of high diversity at low (e.g., Pèrez et al 2015 and high (e.g., KÜlkÖylÜoğlu et al 2012aKÜlkÖylÜoğlu et al , 2016 elevational intervals are also available in the literature.…”
Section: Discussionsupporting
confidence: 90%
“…When we look at the differences in species composition among the elevational intervals subjected herein (Table 3), especially the species with cosmopolitan distribution (e.g., I. bradyi, C. neglecta, P. olivaceus) tend to contribute with high percentages. The average value differences of water temperature and electrical conductivity among elevational intervals herein (see results) strengthened the changing of ecological variables with elevation as proposed previously (KÜlkÖylÜoğlu et al 2012c, McCain & Grytnes 2010Schindler et al 1990). This kind of change explains the conditions in mid and high elevations.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Except a few species (e.g., L. inopinata ), many nonmarine ostracod species reported inhere tend to be found in a variety of aquatic bodies from low to high elevational ranges. Besides, our results support the idea (Külköylüoğlu et al, 2012, 2013; Yavuzatmaca et al, 2017) that increasing tolerance ranges corresponds to decreasing optimum values. Implication of this view is that species (i.e., cosmopolitans) with high tolerance ranges may reduce their optimum requirements for some of those ecological variables or conditions in water bodies to increase their survival abilities.…”
Section: Discussionsupporting
confidence: 89%
“…Reeves et al (2007) indicated the restriction of groundwater ostracods in the Pilbara region of northwestern Australia to mid-altitude locations since water depth, water chemistry, temperature and conductivity are altered by altitude. Külköylüoğlu et al (2012d) and Rogora et al (2008) showed the negative correlation between altitude and conductivity. Similarly, electrical conductivity herein showed a tendency to decrease with increasing elevations.…”
Section: Discussionmentioning
confidence: 92%